Interactions among morphotype, nutrition, and temperature impact fitness of an invasive fly. Issue 5 (3rd February 2019) - Rendon, Dalila; Walton, Vaughn; Tait, Gabriella; Buser, Jessica; Lemos Souza, Ivana; Wallingford, Anna; Loeb, Greg; Lee, Jana
Abstract: Invasive animals depend on finding a balanced nutritional intake to colonize, survive, and reproduce in new environments. This can be especially challenging during situations of fluctuating cold temperatures and food scarcity, but phenotypic plasticity may offer an adaptive advantage during these periods. We examined how lifespan, fecundity, pre‐oviposition periods, and body nutrient contents were affected by dietary protein and carbohydrate (P:C) ratios at variable low temperatures in two morphs (winter morphs WM and summer morphs SM) of an invasive fly, Drosophila suzukii. The experimental conditions simulated early spring after overwintering and autumn, crucial periods for survival. At lower temperatures, post‐overwintering WM lived longer on carbohydrate‐only diets and had higher fecundity on low‐protein diets, but there was no difference in lifespan or fecundity among diets for SM. As temperatures increased, low‐protein diets resulted in higher fecundity without compromising lifespan, while high‐protein diets reduced lifespan and fecundity for both WM and SM. Both SM and WM receiving high‐protein diets had lower sugar, lipid, and glycogen (but similar protein) body contents compared to flies receiving low‐protein and carbohydrate‐only diets. This suggests that flies spend energy excreting excess dietary protein, thereby affecting lifespan and fecundity. Despite having to recover from nutrient depletion after an overwintering period, WM exhibited longer lifespan and higher fecundity than SM in favorable diets and temperatures. WM exposed to favorable low‐protein diet had higher body sugar, lipid, and protein body contents than SM, which is possibly linked to better performance. Although protein is essential for oogenesis, WM and SM flies receiving low‐protein diets did not have shorter pre‐oviposition periods compared to flies on carbohydrate‐only diets. Finding adequate carbohydrate sources to compensate protein intake is essential for the successful persistence of D. suzukii WM and SM populations during suboptimal temperatures. Abstract : At lower temperatures, Drosophila suzukii females do not invest in reproduction and benefit from a carbohydrate‐only diet. With increasing temperatures, low‐protein diets are optimal for fecundity without compromising lifespan. High‐protein diets are detrimental. Post‐overwintering WM have higher lipid and sugar body content than SM and increased lifespan and fecundity.